Hubungan Kondisi Fisik Terhadap Terhadap Mental Toughness pada Olahraga Gulat - Pinem, Swandika; Marpaung, Hakim Irwandi; Mubarak, Muhammad Fitrah; Prasetyo, Muhammad Teguh; Fadhiil , Fahmi; Khasanah, Fachrun Nisa Sofiyah (JSH: Journal of Sport and Health, 2025)
This study aims to analyze the relationship between physical condition (leg muscle strength, waist flexibility, abdominal muscle strength, and arm strength) and mental toughness in wrestling athletes. The research method used was quantitative with a correlational design. The population, which also served as the sample, consisted of 15 athletes selected by a total sampling technique. Data collection instruments included a leg dynamometer for leg strength, a flexibility test for waist flexibility, a sit-up test for abdominal strength, and the MTIid to measure mental toughness. The results of the Shapiro-Wilk normality test and linearity test indicated that the data were normally distributed and had a linear relationship. Hypothesis testing using a correlation test found significant relationships between leg muscle strength (p=0.004), waist flexibility (p=0.005), abdominal muscle strength (p=0.001), and arm strength (p=0.001) with mental toughness. This study concludes that the physical condition, comprising leg muscle strength, waist flexibility, abdominal muscle strength, and arm strength, has a significant relationship with the mental toughness of wrestling athletes. The implication is that wrestling training programs should be designed integratively to develop physical and mental aspects simultaneously.